2015
DOI: 10.1165/rcmb.2014-0294tr
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Derived Growth Factor Signaling in the Lung. From Lung Development and Disease to Clinical Studies

Abstract: Platelet-derived growth factors (PDGFs) and their receptors (PDGFRs) represent one of the most intensively studied families of growth factors in the last four decades. PDGF signaling plays an essential role in cell proliferation, differentiation, migration, and survival. In vivo studies have documented an important role of PDGF signaling in the normal development of several organs, such as the kidney, eye, or lung. PDGF signaling is essential for the formation of intact mesenchymal cells during embryogenesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 256 publications
1
72
0
Order By: Relevance
“…PI3K/Akt and ERK1/2 are two main intracellular signaling pathways activated by PDGF in PASMC proliferation [18]. Therefore, we determined the involvement of these two pathway in PDGF regulation of SphK1/S1P.…”
Section: Pdgf Up-regulates Sphk1 and S1p Expression Via Activation Ofmentioning
confidence: 99%
“…PI3K/Akt and ERK1/2 are two main intracellular signaling pathways activated by PDGF in PASMC proliferation [18]. Therefore, we determined the involvement of these two pathway in PDGF regulation of SphK1/S1P.…”
Section: Pdgf Up-regulates Sphk1 and S1p Expression Via Activation Ofmentioning
confidence: 99%
“…These observations suggest a key role of PAI-1 in the migration of endothelial cells induced by various angiogenic factors. In addition, we assessed whether PAI-1 inhibition by SK-216 affected the phosphorylation of ERK1/2 and AKT, two major downstream signaling targets of VEGF (37), FGF (38), PDGF (39), and HGF (40). Our results showed that the phosphorylation of ERK1/2 and AKT in HUVECs induced by these angiogenic factors, except for HGF-induced phosphorylation of ERK1/2, was not inhibited by SK-216.…”
Section: Discussionmentioning
confidence: 91%
“…Hence, rather than a specific cell type being responsible for FF, it is likely that specific pathways of myofibroblast differentiation and proliferation are essential pathogenic components for FF formation. PDGF has been widely implicated in fibrotic disorders through the regulation of myofibroblast differentiation and proliferation, and BLM mouse models demonstrated that PDGFR signaling can be a promising therapeutic target for preventing lung fibrosis development (12)(13)(14)(15)(29)(30)(31). In terms of clinical relevance of PDGFR signaling in IPF pathogenesis, one of the representative target receptors of nintedanib, a multiple tyrosine kinase inhibitor causing significant reduction in the decline of forced vital capacity for IPF patients, is PDGFR (32).…”
Section: Discussionmentioning
confidence: 99%